2012
DOI: 10.1016/j.jcrysgro.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

An innovative antisolvent precipitation process as a promising technique to prepare ultrafine rifampicin particles

Abstract: a b s t r a c tMany existing and new drugs fail to be fully utilized because of their limited bioavailability due to poor solubility in aqueous media (BCS drug classes II and IV). In this work, for accelerating dissolution of this kind of poorly water-soluble drugs, an antisolvent precipitation method that does not require the use of conventional volatile organic solvents is proposed. To demonstrate this technique, ultrafine particles of rifampicin were prepared using a room temperature ionic liquid (1-ethyl 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 36 publications
(37 reference statements)
2
45
0
1
Order By: Relevance
“…Production of microcrystals refers to the formation of an additional surface area and interfaces. 30 Solubility results showed that the crystals that were prepared using Brij 35 has shown the highest solubility of the drug in water (9.99-41.84 mg/ml) as compared with the untreated drug (0.036 mg/ml) ( Table 2).…”
Section: Saturated Solubilitymentioning
confidence: 99%
“…Production of microcrystals refers to the formation of an additional surface area and interfaces. 30 Solubility results showed that the crystals that were prepared using Brij 35 has shown the highest solubility of the drug in water (9.99-41.84 mg/ml) as compared with the untreated drug (0.036 mg/ml) ( Table 2).…”
Section: Saturated Solubilitymentioning
confidence: 99%
“…If the use of spherical crystallization [46] and the quasi emulsion solvent diffusion (QESD, Fig. 7) method has been well known to improve the properties of active ingredients [47], an antisolvent process involving ionic liquids was used recently to prepare ultrafine rifampicyne particles [48].…”
Section: Particle Engineering Strategies Traditionally Include Top Domentioning
confidence: 99%
“…Micro/nanonization during crystallization (Rasenack and Müller, 2002;Rasenack and Müller, 2004;Badawi et al, 2011;Viçosa et al, 2012), surface modification (Han et al, 2011) and crystal structure modification (Eerdenbrugh et al, 2009) may improve the dissolution rate of poorly water-soluble APIs (Active Pharmaceutical Ingredients).…”
Section: Introductionmentioning
confidence: 99%
“…One goal in this crystallization operation is the control of product properties, e.g., particle size and particle size distribution (Zhao et al, 2007;Zhang et al, 2009), purity, residual solvent content, crystallinity, polymorphic form (Balani et al, 2010) and dissolution rates in specific media during in vitro-tests (Viçosa et al, 2012;Plakkot et al, 2011) to a certain extent. The product properties can be manipulated by changing the process parameters and formulation.…”
Section: Introductionmentioning
confidence: 99%